SRT1720 Alleviates ANIT-Induced Cholestasis in a Mouse Model - Yu, Linxi; Liu, Xiaoxin; Yuan, Zihang; Li, Xiaojiaoyang; Yang, Hang; Yuan, Ziqiao; Sun, Lixin; Zhang, Luyong; Jiang, Zhengzhou (Frontiers in Pharmacology, 2017)
Intrahepatic cholestasis is a kind of clinical syndrome along with hepatotoxicity which caused by intrahepatic and systemic accumulations of bile acid. There are several crucial generating factors of the pathogenesis of cholestasis, such as inflammation, dysregulation of bile acid transporters and oxidative stress. SIRT1 is regarded as a class III histone deacetylase (HDAC). According to a set of researches, SIRT1 is one of the most important factors which can regulate the hepatic bile acid metabolism. SRT1720 is a kind of activator of SIRT1 which is 1000 times more potent than resveratrol, and this paper is aimed to study its protective influence on hepatotoxicity and cholestasis induced by alpha-naphthylisothiocyanate (ANIT) in mice. The findings revealed that SRT1720 treatment increased FXR and Nrf2 gene expressions to shield against hepatotoxicity and cholestasis induced by ANIT. The mRNA levels of hepatic bile acid transporters were also altered by SRT1720. Furthermore, SRT1720 enhanced the antioxidative system by increasing Nrf2, SOD, GCLc, GCLm, Nqo1, and HO-1 gene expressions. In conclusion, a protective influence could be provided by SRT1720 to cure ANIT-induced hepatotoxicity and cholestasis, which was partly through FXR and Nrf2 activations. These results indicated that SIRT1 could be regarded as a therapeutic target to cure the cholestasis.